Single-cell profiling reveals distinct subsets of CD14+ monocytes drive blood immune signatures of active tuberculosis - Hillman, Hannah; Khan, Nabeela; Singhania, Akul; Dubelko, Paige; Soldevila, Ferran; Tippalagama, Rashmi; DeSilva, Aruna D.; Gunasena, Bandu; Perera, Judy; Scriba, Thomas J.; Ontong, Cynthia; Fisher, Michelle; et al. (Frontiers in Immunology, 2023)
Previous studies suggest that monocytes are an important contributor to tuberculosis (TB)-specific immune signatures in blood. Here we carried out comprehensive single-cell profiling of monocytes in paired blood samples of active TB (ATB) patients at diagnosis and mid-treatment, and healthy controls. At diagnosis, ATB patients displayed increased monocyte-to-lymphocyte ratio, increased frequency of CD14+CD16- and intermediate CD14+CD16+ monocytes, and upregulation of interferon signaling genes that significantly overlapped with previously reported blood TB signatures in both CD14+ subsets. In this cohort, we identified additional transcriptomic and functional changes in intermediate CD14+CD16+ monocytes, such as the upregulation of inflammatory and MHC-II genes, and increased capacity to activate T cells, reflecting overall increased activation in this population. Single-cell transcriptomics revealed that distinct subsets of intermediate CD14+CD16+ monocytes were responsible for each gene signature, indicating significant functional heterogeneity within this population. Finally, we observed that changes in CD14+ monocytes were transient, as they were no longer observed in the same ATB patients mid-treatment, suggesting they are associated with disease resolution. Together, our study demonstrates for the first time that both intermediate and classical monocytes individually contribute to blood immune signatures of ATB and identifies novel subsets and associated gene signatures that may hold disease relevance.